2015
DOI: 10.1016/j.cherd.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Purification of slag-derived leachate and selective carbonation for high-quality precipitated calcium carbonate synthesis

Abstract: of slag-derived leachate and selective carbonation for high-quality precipitated calcium carbonate synthesis, Chemical Engineering Research and Design (2015), 104, 180-190. This is a PDF file of an unedited manuscript that has been accepted for publication. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered, which could affect the content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Si can retain metal ions, such as Fe, during its hydration (by forming silica gel), indicating that silica gel affects leaching selectivity. Preventing silica-gel formation by adjusting L/S adversely affects the purity of carbonate minerals, which is in agreement with the results reported by Crom et al [30]. Impurities retained in the silica gel phase, such as Fe, Mn, and Al, were removed by washing with deionized water, affording a high-purity (~99%) amorphous silica powder with a wide specific surface area (several hundred meter square per gram).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Si can retain metal ions, such as Fe, during its hydration (by forming silica gel), indicating that silica gel affects leaching selectivity. Preventing silica-gel formation by adjusting L/S adversely affects the purity of carbonate minerals, which is in agreement with the results reported by Crom et al [30]. Impurities retained in the silica gel phase, such as Fe, Mn, and Al, were removed by washing with deionized water, affording a high-purity (~99%) amorphous silica powder with a wide specific surface area (several hundred meter square per gram).…”
Section: Discussionsupporting
confidence: 80%
“…Huijgen et al [13] have reported that wollastonite (CaSiO 3 ) can be used as a metal Figure 1, JEOL-7800F, Jeol, Tokyo, Japan) used herein was obtained from a steel making company in South Korea; slag was milled, and powders with a mesh size of below 200 were collected. As reported in previous studies utilizing BFS [2,30], crystal phases of BFS were not observed by XRD analysis (Analytical X-ray B.V.X'pert-MPD, Philips, EA Almelo, The Netherlands; scanning range of 3 • -70 • (2θ) (CuKα) using a step size of 0.02 • (2θ) at 40 kV/40 mA). The concentrations of elements in oxide compounds were quantitatively measured by X-ray fluorescence (XRF; MXF-2400, Shimadzu, Kyoto, Japan, approximately 1 g of a sample was used to make a glass disc with 5.5 g of Li 2 B 4 O 7 as the flux) for the estimation of the leaching ratio (LCH.…”
Section: Introductionmentioning
confidence: 75%
“…The results of previous studies of the dissolution of slag using acetic acid [6,8,9] can be summarized as follows:…”
Section: Optimization Of Leaching Parametersmentioning
confidence: 99%
“…Ever since acetic acid (a weak acid with a pKa = 4.7) was shown to be effective for the extraction of Ca from natural calcium silicates in mineral carbonation reactions [4], it has been used as a mild extraction agent for the selective extracting of Ca from BFS [5][6][7][8][9][10]. Most studies regarding the mineral carbonation of BFS are dedicated to the production of relatively pure CaCO 3 following selective Ca dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies regarding the mineral carbonation of BFS are dedicated to the production of relatively pure CaCO 3 following selective Ca dissolution. On the other hand, the other major element present in BFS, namely Si, is considered to be a target material to be extracted as silica gel, along with other impurities during acid dissolution processes [5,8,10]. Temperatures above 50 • C are recommended for the extraction of Ca and the removal of Si during the dissolution process [9].…”
Section: Introductionmentioning
confidence: 99%